2023
DOI: 10.3390/agronomy13041049
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Profile, Nutritional Quality and Microbial Populations of Melon Plant Biomass Silage Ensiled with Corn Bran

Abstract: Currently, there is no use for melon plant biomass in agriculture and animal feeding. Using this biomass as silage provides a more sustainable production system. Thus, the objective of this study was to evaluate the silage produced with different mixtures of melon plant biomass and ground corn. The experimental design was completely randomized in a factorial scheme (5 × 2) with five replications. The treatments consisted of five mixtures of melon plant biomass between the plant (branch + leaf) and the fruit (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The exposure of silages to the aerobic environment reduced the maximum pH registered, and the inclusion of hay increased the time required for the mass to reach the maximum pH. This effect is beneficial for maintaining the nutritional quality of the silage during exposure to air, as aerobic microorganisms use residual fermentation substrates and organic acids from the fermentation process for colonization and population increases in an aerobic environment [ 19 ]. With the inclusion of gliricidia hay up to 20% in cactus pear silages, the TMT increased by approximately 8.4 h compared to the silage of cactus pear alone, with a higher DTS also being observed, resulting in a greater heating capacity of the silage (2.4 °C) and shorter time to break aerobic stability (72 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure of silages to the aerobic environment reduced the maximum pH registered, and the inclusion of hay increased the time required for the mass to reach the maximum pH. This effect is beneficial for maintaining the nutritional quality of the silage during exposure to air, as aerobic microorganisms use residual fermentation substrates and organic acids from the fermentation process for colonization and population increases in an aerobic environment [ 19 ]. With the inclusion of gliricidia hay up to 20% in cactus pear silages, the TMT increased by approximately 8.4 h compared to the silage of cactus pear alone, with a higher DTS also being observed, resulting in a greater heating capacity of the silage (2.4 °C) and shorter time to break aerobic stability (72 h).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the silage of cactus pear alone presented a Na value higher than that presented by silages containing gliricidia hay in its composition, meeting the requirements of beef cattle (0.6–0.8 g/kg) [ 34 ] for this mineral. The high Na content highlights the importance of silage of cactus pear alone for ruminant nutrition, as this mineral plays a key role in maintaining osmotic pressure, acid–base balance, and control of water metabolism [ 19 ]. In addition, Na can reduce feed intake because it increases animal thirst; however, as cactus pear is also a source of water for ruminants, this unfavorable effect of Na is probably minimized.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of corn bran as an additive has shown positive effects on the quality parameters of silages, while the addition of urea has contributed to reducing the yeast population, which is crucial for enhancing the aerobic stability of melon fruits. It was observed that specific fruit quantities (0%, 10%, and 100% fruits) yielded superior quality given indicative parameters in the silages produced [9,10]. These measures present viable options for farmers living in melon-producing regions.…”
Section: Introductionmentioning
confidence: 98%